Conductive heat transfer in lamellar phase change material composites. (September 2020) - Hoe, Alison; Deckard, Michael; Tamraparni, Achutha; Elwany, Alaa; Felts, Jonathan R.; Shamberger, Patrick J.
Highlights: Effective medium and "fin equation" approximations dramatically reduce computational complexity. Finite difference numerical results employed to validate analytical approximations. Characteristic thermal response regimes and critical times are identified. Abstract: Composite thermal energy storage materials consisting of highly thermally conductive and capacitive constituent elements can thermally buffer transient heat pulses. The ability to quantitatively describe these composite systems is valuable in the design of thermal management components to determine how a thermal load affects the necessary geometric aspects. Here, we develop numerical and analytical reduced-order solutions of 1D conductive heat transfer in lamellar multi-component thermal energy storage materials. Investigation of the limit in which conduction is the dominant term is important for the case where length-scales are small enough to limit convection or where the phase change material maintains a solid or high viscosity state at high temperatures. The response of lamellar PCM systems is herein described using (1) an effective medium approximation, and (2) a 1D "fin equation" approximation. Analytical solutions are compared against a higher resolution finite difference analysis numerical model in order to determine the length- and time- scales over which each expression is valid. The result of this work is a set of approximate solutions of transient thermal behavior in thermal energy storage composites, which can aid in the deliberate design of composite thermal energy storage materials to achieve desired performance characteristics. Remarkably, application of this approach predicts composite structures which absorb heat at much higher rates than pure metal conductors.